A new screening method for flunitrazepam in vodka and tequila by fluorescence spectroscopy. (21st February 2012) - Leesakul, Nararak; Pongampai, Sirintip; Kanatharana, Proespichaya; Sudkeaw, Pravit; Tantirungrotechai, Yuthana; Buranachai, Chittanon
ABSTRACT A new screening method for flunitrazepam in colourless alcoholic beverages based on a spectroscopic technique is proposed. Absorption and steady‐state fluorescence of flunitrazepam and its protonated form with various acids were investigated. The redshift of the wavelength of maximum absorption was distinctively observed in protonated flunitrazepam. An emissive fluorescence at 472 nm was detected in colourless spirits (vodka and tequila) at room temperature. 2‐M perchloric acid was the most appropriated proton source. By using electron ionization mass spectrometry and time‐dependent density functional theory calculations, the possible structure of protonated flunitrazepam was identified to be 2‐nitro‐N‐methylacridone, an acridone derivative as opposed to 2‐methylamino‐5‐nitro‐2′‐fluorobenzophenone, a benzophenone derivative. Copyright © 2012 John Wiley & Sons, Ltd.